A PENGARUH VARIABEL MAKROEKONOMI TERHADAP EMISI KARBON DI NEGARA ASEAN 2015-2022 - Maratus Sholikhah; Hastarini Dwi Atmanti (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to test the Environmental Kuznets Curve (EKC) hypothesis in ASEAN member countries from 2015 to 2022 and to analyze the effects of GDP per capita, population, energy transition, foreign investment, and trade openness on carbon emissions in ASEAN countries during the same period, both simultaneously and partially. This research employs a quantitative approach using data sourced from the International Energy Agency and the World Bank. The analytical method used is multiple linear regression with panel data covering 10 ASEAN countries from 2015 to 2022. The results show that the Environmental Kuznets Curve (EKC) hypothesis is confirmed in ASEAN member countries for the period 2015–2022, with a turning point in the relationship between GDP per capita and CO₂ emissions at approximately 17.11 trillion USD. Singapore and Brunei Darussalam are among the ASEAN countries that have passed the scale effect and structural effect phases on the EKC, while the remaining countries are still on the left side of the curve. GDP per capita, population, energy transition, foreign investment, and trade openness simultaneously influence carbon emissions in ASEAN during 2015–2022. GDP per capita can either increase or decrease carbon emissions significantly depending on whether a country has reached the EKC turning point. Population, foreign investment, and trade openness significantly increase carbon emissions in ASEAN. Meanwhile, energy transition tends to reduce carbon emissions, although the effect is not statistically significant. Keywords: Carbon emissions, GDP per capita, energy transition, trade openness